Design Guidelines for Urban Safety - Koca, Tuba; Erkan, Nilgun Colpan (KARE PUBL, 2022)
Ensuring security in urban life is one of the primary needs. In ensuring security in the cities around the world, crime prevention activities through environmental designs are carried out as well as the crime prevention efforts of the police forces. Researches shows that spatial arrangements can create prevention against some crimes, therefore crime and fear of crime can be partially reduced as well. Based on this finding, it is seen that Crime Prevention Through Environmental Design - CPTED Guides are used around the world in crime prevention and security. In this study, CPTED Guides, one of the thematic guides included in the urban design guides, are discussed. Firstly, the study briefly discusses the prominent approaches in ensuring urban security, regarding crime and fear of crime in cities. It focuses on the design guidelines that emerge from these approaches. In this context, two safety-oriented urban design guides, Western Australia and Virginia Beach Guides, were reviewed. The Australian Guide was chosen due to the fact that it is a comprehensive, state-level guide and it includes the principles for the preparation of sub-guides; whereas the choice of The Virginia Beach Guide was due to its local scale. These guides were compared in terms of their purpose, scope, stakeholders, techniques and principles. It is seen that, in Turkey, there has not been a planned or organized environmental design or a study for a guide on urban security yet. For this reason, the information provided by these two guides of different scales are taken into consideration for recommendations on a crime prevention through environmental design guide for Turkish cities.
Keywords: CPTED; crime prevention through environmental design; urban safety theories; urban design guidelines; CRIME; Public Administration